Comparative Analysis of the Polygamy Regulations in Indonesia and Morocco - Trigiyatno, Ali; Rahmawati, Dewi; Utomo, Purwoko; Mujadid (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2023)
The purpose of this essay is to compare and comprehend the similarities and differences in the rules governing polygamy in the countries of Indonesia and Morocco. applying a normative strategy while also utilizing comparative research. Using secondary data sources and involving primary, secondary, and tertiary sources of legal information in the research process. Technique of analysis combined with content analysis. In light of this, the law in Morocco goes one step further in providing the wife the ability to create conditions or a marriage agreement, the objective of which is that she is not willing to be co-opted. Despite the fact that both parties subscribe to polygamy, the law in Morocco goes one step further. The court will not grant the spouse permission to remarry even if he expresses a desire to do so. In Indonesia, one does not find an explicit version of the same regulation. Aside from that, the legislation in Morocco seems to further scare men into not practicing polygamy by beginning the sound of various articles with the phrase